METODE PERHITUNGAN ANALISIS STABILITAS LERENG DENGAN PERKUATAN SHEET PILE MENGGUNAKAN PROGRAM GEOSTRUCTURAL ANALYSIS VERSI 19 (STUDI KASUS LERENG SUNGAI KOMERING DI KABUPATEN OGAN KOMERING ILIR) - Wibrian, Achmad; Setyanto, Setyanto; Siregar, Amril Ma'ruf Siregar Ma'ruf (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Slope stability analysis of Komering River in Ogan Komering Ilir, South Sumatra was done to handle the problem of sliding or scouring at the cliffs which are often found on the outside corner of the river. Komering River is a river with meandering pattern that is very susceptible to scouring on the outside of the bend and sedimentation on the inside of the bend. This research focuses on the study of slope stability analysis with sheet pile used as method. Analysis was conducted using Geostructural Analysis version 19 and was compared to manual calculation.Data analysis on the result of soil testing was performed to identify soil properties. The obtained results were then used in slope stability analysis. Slope stability analysis was performed in two conditions maximum groundwater level and normal groundwater level using Bishop method and Fellenius method. The results of manual calculation were then compared with the results of Geostructural Analysis Program Version 19. Sheet pile was selected as slope stabilization measures. Analysis after stabilization is done with the same steps as analysis before stabilization.The results from the two methods showed a quite significant difference. The results obtained from Bishop method before stability measure and after stability measure were 1,018 and 4,23 respectively. Whereas, the results obtained from Fellenius method before stability measure and after stability measure were 0,75 and 3,42 respectively. Based on these results, it can be concluded that sheet pile is an effective slope stability measure.Keywords: Slope stability, Geostructural Analysis Program, Bishop, Fellenius, Sheet Pile.